"Dada South? Experimentation, Radicalism and Resistance": Dada's Legacies from South African Perspectives. Issue 2 (2nd September 2017) - Toussaint, Denise
Abstract: In 2016, the art world celebrated the Dada centenary with festivities all over the globe; the interest in the European avant-garde movement appears stronger than ever. As long as six years ago, the exhibition "Dada South? Experimentation, Radicalism and Resistance" took place in the Iziko South African National Gallery in Cape Town and made a significant contribution to the discourse on Dada in the global context. "Dada South?" opened up an intriguing position in a highly topical discourse. The show engaged in central issues of the current discussions on global art practice and opened the view to the North-South axis of Dadaist practice. The exhibition considered Dada's legacies in relation to performance, counter-rational strategies, collectivity, deconstruction, and resistance in South African art practice and discursively engaged in the discussion of a global understanding of art and art history. However, the show was barely noticed in the international context. Especially regarding the current interest in Dada, and in the context of the discourse on global art and exhibition practice, "Dada South?" must be brought into focus. In this paper, the exhibition design and objective are analysed and the significance of the exhibition in the global context is addressed.